2005
DOI: 10.1577/h03-065.1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Studies of Florfenicol in Koi Carp and Threespot Gourami Trichogaster trichopterus after Oral and Intramuscular Treatment

Abstract: The pharmacokinetics of florfenicol were studied in koi carp Cyprinus carpio (hereafter, koi) and threespot gourami Trichogaster trichopterus after oral (50 mg/kg) and intramuscular (25 mg/kg) administration of the drug in warm water conditions (24-25ЊC). The estimates of clearance, volume of distribution, and half-life were 0.05 L · h Ϫ1 · kg Ϫ1 , 1.0 L/kg, and 16 h, respectively, in koi. In threespot gourami, the corresponding estimates were 0.32 L · h Ϫ1 · kg Ϫ1 , 2.0 L/kg, and 4 h. In koi, minimal drug abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 8 publications
2
45
3
1
Order By: Relevance
“…, respectively (Shen and Wu, 2002;Samuelsen et al, 2003;Yanong and Cuds, 2005). This experiment showed that the CL of florfenicol in healthy and infected P. crocea serum were 0.32 L kg −1 ·h −1 and 0.45 L kg −1 ·h −1 , respectively.…”
Section: Discussionmentioning
confidence: 65%
“…, respectively (Shen and Wu, 2002;Samuelsen et al, 2003;Yanong and Cuds, 2005). This experiment showed that the CL of florfenicol in healthy and infected P. crocea serum were 0.32 L kg −1 ·h −1 and 0.45 L kg −1 ·h −1 , respectively.…”
Section: Discussionmentioning
confidence: 65%
“…In other literatures, the application of florfenicol has been recommended for bacterial diseases in aquaculture, e.g., vibriosis in cod (Gadus morhua) (Samuelsen and Bergh, 2004), enteric septicemia in pond-reared channel catfish fingerlings (Gaunt et al, 2006), furunculosis and vibriosis in Atlantic salmon (Nordmo et al, 1998), and furunculosis in Atlantic salmon (Inglis et al, 1991;Samuelsen et al, 1998). Though florfenicol was closely related to chloramphenicol, it has been proven to be effective in combating chloramphenicol-resistant bacteria species (Yanong et al, 2005). In addition, florfenicol is currently being registered for use in food fish in the United States due to its lack of the functional group associated with human toxicity (Yanong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Though florfenicol was closely related to chloramphenicol, it has been proven to be effective in combating chloramphenicol-resistant bacteria species (Yanong et al, 2005). In addition, florfenicol is currently being registered for use in food fish in the United States due to its lack of the functional group associated with human toxicity (Yanong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetically, florfenicol use has been reported among some species of fish such as Atlantic salmon (Salmo salar), in which a bioavailability of more than 95% is present, exhibiting a good distribution among all of the organs and tissues. Its halflife in fish is less than 15 h (Yanong & Curtis, 2005). However, published information for shrimp is scarce, meaning that the kinetic behavior of this compound among these crustaceans has not yet been completely elucidated.…”
Section: Florfenicolmentioning
confidence: 99%